2021
DOI: 10.1021/acs.langmuir.1c01796
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Stabilization of a Bulk Nanobubble: A Molecular Dynamics Analysis

Abstract: Bulk nanobubbles (NBs) have received considerable attention because of their extensive potential applications, such as in ultrasound imaging and water management. Although multiple types of experimental evidence have supported the existence and stabilization of bulk NBs, the underlying mechanism remains unclear. This study numerically investigates the bulk NB stabilization with molecular dynamics (MD) methods: the all-atom (AA) MD simulation is used for NBs of several nanometers diameter; the coarse-grained (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 67 publications
6
24
0
Order By: Relevance
“…With regard to the high inner-density model that the lifetime of UFBs is longer as the density inside a bubble is higher, experimental evidence is required [38]. As the existence of the boundary layer of a UFB has been confirmed experimentally [39], its role on stability of a UFB should be studied further [40,41]. Other models for the stability of a UFB are discussed in Refs.…”
Section: Stability 21 Introductionmentioning
confidence: 99%
“…With regard to the high inner-density model that the lifetime of UFBs is longer as the density inside a bubble is higher, experimental evidence is required [38]. As the existence of the boundary layer of a UFB has been confirmed experimentally [39], its role on stability of a UFB should be studied further [40,41]. Other models for the stability of a UFB are discussed in Refs.…”
Section: Stability 21 Introductionmentioning
confidence: 99%
“…While direct experimental observations are lacking, molecular simulation is a great tool for gaining important insights into the interfacial properties of gas clusters and the stability of bulk nanobubbles. However, expensive computational overhead has heretofore hindered the analysis of nanobubbles with radii larger than tens of nanometers …”
Section: Introductionmentioning
confidence: 99%
“…During the last 20 years, the stability of interfacial nanobubbles (INB) has been attributed to surface pinning, gas oversaturation conditions, high gas epitaxial layering density, and nonuniform gas solubility in the water region. Nonetheless, these explanations were derived from fluid–solid interactions, which are not necessarily sufficient to explain the existence of bulk nanobubbles. Indirect experimental observations have verified that the material inside BNBs is fluid; however, speculations abound as to whether the fluid is a gas or liquid. ,, Researchers have posited a number of theories to explain the stability of BNBs. , One hypothesis proposed the Tolman effect, wherein interfacial tension decreases proportionally to the size of the bubble. However, this size-dependent contribution remains insignificant unless the bubble size is less than 1 nm .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Weijs et al have shown that supersaturation of the surrounding medium stabilizes the NBs. Gao et al have demonstrated the presence of EDL of thickness ∼10 Å. The surface charges are present due to the orientation of water around the NBs.…”
Section: Introductionmentioning
confidence: 99%